1999
DOI: 10.1111/j.1699-0463.1999.tb01560.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of hydrocarbon chain length, pH, and temperature on the binding and bactericidal effect of amphiphilic betaine esters on Salmonella tvphimurium

Abstract: Ahlstrom, B., Thompson, R. A. & Edebo, L. The effect of hydrocarbon chain length, pH, and temperature on the binding and bactericidal effect of amphiphilic betaine esters on Sulmonella typhimurium. APMIS 1999; 107:3 18-24. Amphiphilic betaine esters are quaternary ammonium compounds (QAC) with rapid microbicidal action. They are often labeled 'soft antimicrobial agents', since the compounds hydrolyze spontaneously into betaine and fatty alcohols, thus not only losing their surface active properties and toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 15 publications
2
50
1
Order By: Relevance
“…Thus, for Gram-negative bacteria, the outer membrane of the cell wall acts as an additional barrier to foreign molecules. Previous results have shown that QACs tend to be more effective toward Gram-positive bacteria than Gram-negative bacteria [36,38]. However, the data shown in Figs.…”
Section: Antimicrobial Activity Of Q-posss In Aqueous Solutioncontrasting
confidence: 71%
“…Thus, for Gram-negative bacteria, the outer membrane of the cell wall acts as an additional barrier to foreign molecules. Previous results have shown that QACs tend to be more effective toward Gram-positive bacteria than Gram-negative bacteria [36,38]. However, the data shown in Figs.…”
Section: Antimicrobial Activity Of Q-posss In Aqueous Solutioncontrasting
confidence: 71%
“…It is well known that quaternary ammonium compounds achieve biocidal action by disrupting the cell membrane, and studies have suggested that this kill mechanism can be affected by charge interactions. 11 Other authors have shown that charge-transfer reactions can strongly influence the activity of such biocidal agents. 12,13 Interestingly, it was cetylpyridinium chloride and benzalkonium chloride that showed reversible conversion to the neutral amine in pH12 washing conditions; this ability to lose and gain charge may give rise to the anti-microbial properties displayed in this work.…”
Section: Anti-fungal Activity Of Treated Polyester Fabricsmentioning
confidence: 99%
“…A similar trend was observed in a previous study of QACs by Gélinas et al (16), where the activity between 4°C and 50°C increased with rising temperature and longer contact times. Ahlström et al (3) previously observed that amphiphilic betaine esters (QACs) at 0°C were less active than at 30°C even though binding affinities remained unchanged. The reduction in killing was believed to be due to the reduced fluidity of the outer membrane of Salmonella enterica serovar Typhimurium.…”
Section: Fig 7 Leakage Of Potassium (}) and 260-nm-absorbing (■) Mamentioning
confidence: 99%